Determining heavy metal concentrations and physicochemical properties in wastewater - Hailu Reta; Nibret Mekonen (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2023)
Wastewaters are frequently harmful to both the environment and human health since they are both directly and indirectly released into surface waters. The aim of this study was to determine physicochemical properties and to assess the levels of heavy metals in wastewater. Wastewater samples were collected from Koka and Mojo from the Oromia region, Ethiopia. Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) was used to determine the concentration of these heavy metals. The conductivity of wastewater obtained from the Mojo and Koka sites ranged from 1141.33 to 1498.32µS/cm and 1066.33 to 1243.72µS/cm, respectively. The maximum and minimum BOD effluent from Mojo and Koka sites were 1044.78mg/L and 794.73mg/L, and 883.00mg/L and 772.67mg/L, respectively. The COD value was found to range between 1466.08mg/L and 1615.38mg/L in the Mojo area and 1352.65mg/L to 1530.83mg/L in the Koka area, respectively. High BOD levels are a sign of contamination and could indicate a lack of oxygen for living things. In every one of the sample sites, it exceeds the recommended level. High COD levels suggest hazardous conditions and the presence of organic compounds that are resistant to biological processes. The maximum TDS of the effluents, which is more than the recommended limit, were found to be 2417.08mg/L and 2317.06mg/L in Mojo and Koka areas, respectively. Overall concentrations of heavy metals (As, Pb, B, Zn, Cd Hg, Cu, Ni, Co, Fe, Mn and Cr) in mg/L were found to be in the permissible range except for mercury (Hg). The wastewater had heavy metal Hg that was higher than the limits advised by the WHO and US EPA. The studies' findings imply that the effluents are harmful by nature and need considerable treatment before being released into the ecosystem on land.